The role of pride in women with anorexia nervosa: A grounded theory study. (3rd May 2017) - Faija, Cintia L.; Tierney, Stephanie; Gooding, Patricia A.; Peters, Sarah; Fox, John R. E.
Abstract : Objective: Theory and clinical literature suggest that pride may play an important role in the maintenance of restrictive eating disorders. A grounded theory study explored experiences of, and reflections on, pride among women with a current or past diagnosis of anorexia nervosa. Design: This is a qualitative study using grounded theory. Method: Semistructured interviews were conducted with 21 women recruited from an eating disorder unit in England, and from a UK self‐help organization. Grounded theory from a constructivist lens was used. Analysis involved coding, constant comparison, and memo‐writing. Results: Pride evolves over the course of anorexia nervosa. Two overarching conceptual categories were identified: 'pride becoming intertwined with anorexia' and 'pride during the journey towards recovery'. These categories encompassed different forms of pride: 'alluring pride', 'toxic pride', 'pathological pride', 'anorexia pride', 'shameful pride', 'recovery pride', and 'resilient pride'. Initially, pride contributed to self‐enhancement and buffered negative emotions. As the condition progressed, pride became a challenge to health and interfered with motivation to change. During recovery, perceptions of pride altered as a healthy approach to living ensued. Conclusions: The evolving nature of pride plays a central role in development, maintenance, and treatment of anorexia nervosa. Understanding of pride and its role in psychotherapeutic work with this client group may increase motivation to change and promote recovery. Future work should investigate whether tackling pride in eating disorders increases treatment efficacy and reduces the risk of relapsing. Practitioners points: Pride associated with anorexia appeared to evolve in nature. During early stages of the eating disorder, it stopped people from seeking help. Later on, it prevented them from seeing pride in healthy domains of life (outside anorexia). Over time, pride in anorexia became an overwhelming emotion that interfered with motivation to change. It is important for practitioners to assess and discuss pride in anorexia and its evolving nature during treatment. Understanding of pride and its role in psychotherapeutic work with this client group may increase motivation to change and promote recovery.